Environmental cues that affect knowing: A case Study in a public hospital building - Garip, Ervin (Elsevier Science Bv, Sara Burgerhartstraat 25, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2011)
Hospital buildings can be described as sophisticated public areas due to their functional organizations. complexity and architectural configuration. Although these buildings generally cover all the functional requirements, quite often they are not able to face the psychological needs of patients and their companions. The research which is presented in this article focuses on the "perceptive memories" of companions, during their visits in the hospital. The main aim of the study is to describe the "visual characteristics" of the environment that helps the users to "know" the building and affect the "legibility". The case study was carried out in one of the largest public hospitals in Istanbul, the CAPA Clinical Faculty, which has a distinctive architectural form. The symmetrical plans of the building provided an opportunity to compare data gathered from the different departments of the hospital which have very similar configurations but different wall colours, signage systems, functions, lighting design, floor coverings and landmarks. 41 participants were engaged in a questionnaire task, which contained open-ended questions, and photographs taken from similar points and presented the same perspectives that were chosen on purpose. The participants were asked to choose their departments from the picture boards and explain the reason for their choice by describing the physical characteristics of the environment. In the literature, these mentioned points are called "choice points", places where people get information from the environment and make decisions about their movements. As a result of the study, the analysis of the data provided support that people need environmental cues for describing and knowing their environment. The results essentially present the fact that legibility decreases in conditions in which there are fewer environmental cues. The research also suggests that the time spent in the hospital plays a significant role in the task performance. People who spent more time in the hospital tended to use different descriptive words from others. One of the most significant purposes of architectural design is to create environments in which users are psychologically satisfied with the human-environment interaction system. It is essential that the organization of the physical environment satisfies peoples. psychological needs, particularly in public places such as hospital buildings, where people don't have time and energy to waste. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the 2nd World Conference on Psychology, Counselling and Guidance.
Keywords: Psychological Needs; Perceptive Memory; Legibility; Experiencing Lospitals; Psikolojik İhtiyaçlar; Algısal Bellek; Okunabilirlik; Yaşandığı Hastaneler